Entrepreneurial network organization in theory and practice - Mohd Rosli Mohamad (Universiti Malaysia Kelantan, 2013)
The upsurge of interest of the scholars on entrepreneurship in the last few decades has been the unprecedented increase in the number of studies in this area. Consequently, entrepreneurship in the literature becomes elusive as different scholars see it differently. The worst part is that the literature fails as yet to integrate the concept of entrepreneurship, network and organization into a single framework,Coining the Entrepreneurial Network Organization concept, this paper shows how the entrepreneur as a prime dynamic factor adapt to his need and the environment changes, which ultimately shapes certain forms of organization. Industrial districts, business groups, strategic alliances and subcontracting in industrial production have characteristics of the organizational concept and warrant special attention in this paper.